Variety of shopping modes: theoretical framework, pivotal factors, and managerial implications - Redondo, Ignacio; Charron, Jean-Philippe (Journal of Business Economics and Management, 2023)
With the development of e-commerce and smartphones, consumers can use a variety of shopping modes (i.e., showrooming, webrooming, and completely offline/online shopping), each of which provides specific advantages in terms of price, assortment, service, etc. Using a great variety of these shopping modes can confer many benefits. However, previous studies have found evidence of sizable segments of consumers who typically avoid using a great variety of shopping modes. To understand the contrast in consumers’ variety of shopping modes, we propose a theoretical framework and measure the effect of the desired variety in the information-seeking and purchase processes. Results – from a representative sample of the Spanish consumers – confirm that the variety of shopping modes pivots on the extent to which e-commerce use, smartphone use, offline and online interactivity, and online device interchangeability differ. Better understanding the variety of shopping modes may help marketers adjust their channel strategies to the actual preferences of different consumer segments and assess the economic viability of an omnichannel approach.